Evaluation of a brand from the consumer’s perspective and its relationship with business sustainability (Revista "Boletín el Conuco", 2021)
This manuscript aims to determine the influen- ce of brand equity on the repurchase intentions of a product in such a way that it contributes to business sustainability. The study is based on the general concepts of brand equity with its dimensions: loyalty, notoriety, perceived quality, associations and market behaviour. The empiri- cal study uses a quantitative approach in which data from 321 surveys are processed. The results of the correlations between the dimensions of brand value with the dependent variable repur- chase intention are analyzed. The results of the study suggest a positive relationship, but with astatistical mean value, indicating that these two variables are significantly related. The data reveal that the dimension with the highest relationship is the one corresponding to the associations, while the variable with the lowest relationship is loyalty. It is concluded that the knowledge of the consumers’ perceptions about brands, allows the adoption of measures leading to business sustai- nability in the long term.
Keywords: Consumer, business sustainability, brand.